The N&P Co‐doped Lotus Root Derived Carbon Materials for Highly Sensitive Electrochemical Analysis of Baicalein and Luteolin - Lu, Youluan; Mu, Xinwei; Liu, Yaopeng; Gao, Yi; Shi, Zhen; Zheng, Yin; Huang, Wensheng (Electroanalysis (New York, N.Y.), 2023)
The application of biomass‐based carbon materials in electrochemical sensing was limited due to their few active sites. So N and P double doped biomass pyrolytic carbon materials were designed in this paper. These gained materials were characterized by a series of characterization test techniques, and used as electrode modification to construct electrochemical sensors to detect baicalein (BA) and luteolin (LU). Under the best test condition, the minimum detectability of BA and LU was (7.8±0.25)×10−9 mol/L and (7.6±0.24)×10−9 mol/L (S/N=3), respectively. And the sensor performed well in the Shuanghuanglian oral liquid and the healthy human urine samples.